WASIAT SEBAGAI SARANA PERLINDUNGAN HAK AHLI WARIS: STUDI KASUS PUTUSAN PENGADILAN AGAMA DI INDONESIA (STUDI PUTUSAN PENGADILAN AGAMA SBY No. 3562/Pdt.G/PA.SBY/2023) - Saputra, Ahmad Dani Agustian; Cahyani, Diah; Reyhana, Reyhana (Journal Education and Government Wiyata, 2025)
This study examines the settlement of inheritance disputes based on Surabaya Religious Court Decision Number 3562/Pdt.G/PA.SBY/2023. The case involved the third wife of the late Munir, who was in dispute with the heirs of his first and second wives regarding a plot of land owned by the testator before his marriage to his third wife. In Islamic law, the distribution of inheritance cannot be carried out before other obligations are settled, namely funeral costs, debt repayment, and the execution of a will. A will itself is seen as part of inheritance law that functions to complement the provisions of faraidh. In Indonesian positive law, wills are regulated in the Compilation of Islamic Law (KHI) and are the absolute authority of the Religious Courts based on Law Number 7 of 1989 and its amendments. This study uses a normative juridical method by examining laws and regulations, literature, and court decisions. The results show that the Religious Court has the authority to determine who the legitimate heirs are, determine the inheritance, and regulate the share of each heir. Inheritance disputes that arise are generally related to differences of opinion regarding the status of inherited property and joint property, especially in multiple marriages.